Exploring the Brazilian pediatric palliative care network: a quantitative analysis of a survey data - Esther Angélica Luiz Ferreira; Cristina Ortiz Sobrinho Valete; Silvia Maria de Macedo Barbosa; Graziela de Araujo Costa; Poliana Cristina Carmona Molinari; Simone Brasil de Oliveira Iglesias; Ana Cristina Pugliese de Castro (Revista Paulista de Pediatria, 2023)
Abstract Objective: The aim of this study was to identify the characteristics of services in Brazil that compound the Brazilian Pediatric Palliative Care (PPC) Network. Methods: An online survey was conducted among representatives from PPC services. A total of 90 services from Brazil completed the online survey and answered a questionnaire about the service’s characterization, health professionals working in PPC, access to opioid prescription and education, and research in PPC. Results: In total, 80 services (88.9%) were created after 2010, 52 (57.9%) were in the southeast region, 56 (62.2%) were in public hospitals, 63 (70%) had up to 100 beds, and 57 (63.3%) were at the tertiary level. Notably, 88 (97.8%) had a physician in the team and 68 (75.5%) dedicated part-time to PPC. Also, 33 (36.7%) revealed concern with the care of health professionals and 36 (40%) reported difficulty or no access to opioid prescription. Research studies were reported to be conducted in 29 (32.2%) services. Conclusions: This mapping points out to a concentration of PPC services in the southeast region, with part-time professional dedication, and the need to improve professionals’ care. Difficulty in opioid access was reported. It is necessary to extend PPC participation to other Brazilian regions, increase time dedicated to PPC, improve professionals’ care and improve access to opioid prescription.